Preparation method of FeCrAlY coating
Through plasma glow-assisted cleaning, arc ion plating and high-energy pulse magnetron sputtering technology, combined with gradient coating method, FeCrAlY coating with high film-based binding force, high temperature resistance, corrosion resistance and self-healing performance was prepared, which solved the problems of low film-based binding force and insufficient self-healing ability in the existing coating preparation methods.
Patent Information
- Application Number
- CN202411950624.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing FeCrAlY coating preparation methods have high porosity, large particles and rough surfaces, resulting in low film-based binding force, poor high-temperature corrosion resistance and insufficient self-repair ability.
The substrate is activated by plasma glow-assisted cleaning technology, arc ion plating and bias-assisted Al ion suction embedded substrate, and combined with high-energy pulse magnetron sputtering technology and gradient coating method, a dense, self-healing FeCrAlY coating is prepared.
It significantly improves the membrane-based bonding force, enhances the coating's high temperature resistance, corrosion resistance and self-repair performance, extends its service life and improves stability.
Smart Images

Figure HDA0005214783510000011 
Figure HDA0005214783510000021 
Figure HDA0005214783510000031
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material surface treatment, and in particular to a method for preparing a FeCrAlY coating. Background Art
[0002] For the preparation of FeCrAlY coatings, the commonly used methods currently include low-pressure plasma spraying and pulsed electron beam deposition (GESA). The FeCrAlY coating prepared by low-pressure plasma spraying technology has a high porosity and the presence of large particles and relatively large spray droplets, which makes the surface of the coating relatively rough and porous, resulting in low film-base bonding. Under the action of cyclic thermal stress, the coating is easy to fall off and has poor high-temperature corrosion resistance. In contrast, pulsed electron beam remelting technology can provide better film-base bonding, but the technology is not yet mature and has not yet been commercialized.
[0003] Magnetron sputtering is a type of physical evaporation technology that can be used to prepare multiple materials such as metals, semiconductors, and insulators. It has the advantages of high film formation rate, low substrate temperature, and large-area coating. It is widely used in the preparation of ultra-hard wear-resistant coatings, corrosion-resistant coatings, anti-friction lubricating coatings, optical coatings, etc. required in industry. However, when using traditional magnetron sputtering technology to prepare FeCrAlY coatings, the sputtered metal mostly exists in an atomic state, the metal ionization rate is low (1-10%), the deposition rate and density of the coating are low, the film-base bonding is poor, the coating is easy to peel off and fail, the high-temperature corrosion resistance is insufficient, and the self-repair ability of the coating after wear is poor, and the service life is short. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the objects of the present invention is to provide a method for preparing a FeCrAlY coating; the second object of the present invention is to provide a FeCrAlY coating; the third object of the present invention is to provide an application of the FeCrAlY coating.
[0005] The basic principle of the present invention is described as follows:
[0006] 1) The present invention uses plasma glow assisted cleaning technology (AEGD) to clean the substrate. The high ionization rate plasma is activated by the arc target, and the working gas ions are attracted to bombard the substrate in combination with the anode and bias voltage, so that the substrate is activated without being polluted, and the film-substrate bonding force can be effectively enhanced;
[0007] 2) Arc ion plating and bias-assisted Al ions are attracted to bombard the substrate, so that the Al element is pre-buried within a few microns below the substrate surface. The pre-buried Al element can diffuse to the surface as a supplement when the coating is damaged by friction, etc., and re-form a dense oxide protective layer, thereby achieving self-repair of damaged coatings, extending service life, and improving stability;
[0008] 3) High-energy pulsed magnetron sputtering technology (HiPIMS) can achieve a high ionization rate (>50%) by using a higher pulse peak power (2-3 orders of magnitude higher than conventional magnetron sputtering) and a lower pulse duty cycle (0.5%-10%), making the coating surface smooth and free of particle defects, while controlling the coating microstructure to obtain excellent film-base bonding, reduce coating internal stress, and improve coating density and uniformity; on this basis, a power supply mode that combines a DC power supply with a high-energy pulse power supply is used for coating, which can increase the deposition rate while ensuring high-density, high-bonding coating performance;
[0009] 4) The gradient coating method can effectively utilize the composition and structural characteristics of the alloy to adjust the density of different film layers, so that the density of the surface film layer is relatively low, thereby effectively utilizing the Cr and Al elements in the alloy to form a dense oxide film α-Al in the case of contact with oxygen. 2 O 3 and Cr 2 O 3 , thereby achieving a self-repairing effect; making the film layer close to the substrate side dense enough can effectively prevent oxidation products and corrosive liquid from corroding the substrate and causing cracks, thereby optimizing corrosion resistance; through gradient coating, the substrate protection, film-base bonding strength improvement and internal stress reduction can be achieved simultaneously, making the film layer not easy to peel off under cyclic thermal stress and having excellent heat resistance.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is:
[0011] A first aspect of the present invention provides a method for preparing a FeCrAlY coating, comprising the following steps:
[0012] S1. In a magnetron sputtering device provided with a FeCrAlY magnetron target, an Al arc target and a substrate, the substrate is subjected to plasma glow assisted cleaning to obtain an activated substrate;
[0013] S2, using arc ion plating and bias voltage to attract Al ions to bombard and inject into the activated substrate to obtain an aluminum-rich substrate;
[0014] S3. Using high-energy pulse and DC composite magnetron sputtering method, gradient sputtering coating is performed on the surface of the aluminum-rich substrate, and annealing is performed to obtain the FeCrAlY coating.
[0015] In some embodiments of the present invention, the substrate comprises ferrite, martensitic steel, austenitic steel, zirconium alloy or titanium alloy.
[0016] In some specific embodiments of the present invention, the substrate includes a 306 steel sheet, a 316L steel sheet, a T91 steel sheet or an EP823 steel sheet.
[0017] In some embodiments of the present invention, the substrate in step S1 undergoes surface pretreatment; the surface pretreatment includes increasing or decreasing the surface roughness of the substrate, cleaning and drying.
[0018] In some embodiments of the present invention, reducing the surface roughness comprises grinding the substrate.
[0019] In some embodiments of the present invention, the increasing the surface roughness comprises sandblasting the substrate.
[0020] In some embodiments of the present invention, the cleaning solvent includes an organic solvent or water.
[0021] In some embodiments of the present invention, the organic solvent comprises alcohol and ketone.
[0022] In some specific embodiments of the present invention, the organic solvent includes ethanol and acetone.
[0023] In some embodiments of the present invention, the cleaning time of a single solvent is not less than 10 minutes.
[0024] In some specific embodiments of the present invention, the cleaning time of a single solvent is 10-15 minutes.
[0025] In some embodiments of the present invention, in step S1, the FeCrAlY magnetron target comprises the following components in mass percentage: Fe 60-70wt%, Cr 20-30wt%, Al 4-20wt%, Y 0-0.5wt%.
[0026] In some specific embodiments of the present invention, in step S1, the FeCrAlY magnetron target includes the following components in mass percentage: Fe 60-68wt%, Cr 20-28wt%, Al 4-15wt%, Y 0-0.5wt%.
[0027] In the present invention, the FeCrAlY magnetron target contains Cr and Al elements, which can form a dense oxide film Cr on the substrate surface when in contact with oxygen. 2 O 3 and α-Al 2 O 3 , self-repair of the coating can be achieved by utilizing target elements.
[0028] In some embodiments of the present invention, step S1 includes adjusting the distance between the Al arc target and the substrate, adjusting the background vacuum, temperature, working gas pressure, and arc target power supply, anode power supply and bias power supply parameters of the device to perform plasma glow assisted cleaning of the substrate.
[0029] In some embodiments of the present invention, in step S1, the distance between the Al arc target and the substrate is 5-15 mm.
[0030] In some specific embodiments of the present invention, in step S1, the distance between the Al arc target and the substrate is 8-12 mm.
[0031] In some embodiments of the present invention, in the step S1, the substrate is in a state of self-rotation in front of the Al arc target.
[0032] In the present invention, by adjusting the distance between the Al arc target and the substrate, at a very close target distance, the arc target is used to activate high ionization rate plasma, and the anode and bias are combined to attract protective gas to bombard the substrate, so that the substrate can be activated without being contaminated and the film-substrate bonding strength can be effectively improved.
[0033] In some embodiments of the present invention, in step S1, the background vacuum degree is 1×10 -5 Pa-1×10 -3 Pa.
[0034] In some specific embodiments of the present invention, in step S1, the background vacuum degree is 5×10 -4 Pa-5×10 -3 Pa.
[0035] In some embodiments of the present invention, in step S1, the temperature is 200-600°C.
[0036] In some specific embodiments of the present invention, in step S1, the temperature is 300-500°C.
[0037] In some embodiments of the present invention, in step S1, the working gas pressure is 1-4Pa.
[0038] In some specific embodiments of the present invention, in step S1, the working gas pressure is 1-2Pa.
[0039] In some embodiments of the present invention, the step S1 includes introducing a protective atmosphere into the magnetron sputtering device and adjusting the working gas pressure.
[0040] In some embodiments of the present invention, in step S1, the protective atmosphere includes an inert gas.
[0041] In some specific embodiments of the present invention, the inert gas includes argon.
[0042] In some embodiments of the present invention, in step S1, the arc target power supply is a DC 60-80A.
[0043] In some specific embodiments of the present invention, in step S1, the arc target power supply is a DC power of 70-80A.
[0044] In some embodiments of the present invention, in step S1, the anode power supply is a DC power supply of 40-60A.
[0045] In some specific embodiments of the present invention, in step S1, the anode power supply is a DC power of 45-55A.
[0046] In some embodiments of the present invention, in step S1, the bias power supply has a bias voltage of 300-600V, a frequency of 80-120kHz, and a pulse width of 5-12μs.
[0047] In some specific embodiments of the present invention, in step S1, the bias power supply has a bias voltage of 400-500V, a frequency of 90-110kHz, and a pulse width of 5-10μs.
[0048] In some embodiments of the present invention, the time of the plasma glow assisted cleaning in step S1 is 0.5-1.5 hours.
[0049] In some specific embodiments of the present invention, the time of the plasma glow assisted cleaning in step S1 is 0.5-1h.
[0050] In some embodiments of the present invention, the step S2 includes adjusting the arc target power supply of the device to DC 80-120A.
[0051] In some specific embodiments of the present invention, the step S2 includes adjusting the arc target power supply of the device to a DC 90-110A.
[0052] In some embodiments of the present invention, step S2 includes adjusting the bias power supply of the device to a bias voltage of 700-1000V, a frequency of 80-120kHz, and a pulse width of 5-12μs.
[0053] In some specific embodiments of the present invention, the step S2 includes adjusting the bias power supply of the device to a bias voltage of 700-900V, a frequency of 90-110kHz, and a pulse width of 5-10μs.
[0054] In some embodiments of the present invention, the time for attracting Al ions for bombardment injection in step S2 is 1-2.5 hours.
[0055] In some embodiments of the present invention, the time for attracting Al ions for bombardment injection in step S2 is 1-2 hours.
[0056] In the present invention, the distance between the Al arc target and the activated substrate is small, and Al ions are attracted to bombard the substrate by high-energy arc ion plating and strong bias voltage, so that Al elements can be embedded in the substrate. When the coating surface is damaged by friction, the embedded Al elements can diffuse to the coating surface as element supplement to generate α-Al again. 2 O 3 Oxide film can realize self-repair of damaged coating and extend the service life of coating.
[0057] In some embodiments of the present invention, in step S3, the gradient sputtering coating at least includes respectively adjusting the parameters of the high-energy pulsed magnetron sputtering power supply, the DC power supply and the bias power supply to perform one-stage sputtering coating and two-stage sputtering coating; the first-stage sputtering coating has a deposited film thickness of 13-18 μm; the second-stage sputtering coating has a deposited film thickness of 5-12 μm.
[0058] In the present invention, by adopting the gradient sputtering coating method, the density of different film layers can be controlled by controlling the plating conditions of different film layers, thereby achieving the adjustment of the internal stress of the coating, and effectively improving the high temperature resistance and corrosion resistance of the coating.
[0059] In some specific embodiments of the present invention, the deposition film thickness of the sputtering coating is 13-15 μm.
[0060] In some specific embodiments of the present invention, the deposition film thickness of the two-stage sputtering coating is 8-12 μm.
[0061] In some embodiments of the present invention, during the sputtering coating, the average power density of the high energy pulsed magnetron sputtering power supply is 0.8-1.5 kw / cm 2 , peak power density is 15-25kw / cm 2 , frequency is 100-600Hz, pulse width is 100-200μs.
[0062] In some specific embodiments of the present invention, in the above-mentioned sputtering coating, the average power density of the high-energy pulsed magnetron sputtering power supply is 0.8-1.2 kw / cm 2 , peak power density is 18-22kw / cm 2 , frequency is 100-300Hz, pulse width is 100-150μs.
[0063] In some embodiments of the present invention, during the sputtering coating, the average power density of the DC power supply is 0.5-1.5 kw / cm 2 .
[0064] In some specific embodiments of the present invention, during the sputtering coating, the average power density of the DC power supply is 0.8-1.2 kw / cm 2 .
[0065] In some embodiments of the present invention, in the sputtering coating step, the bias voltage of the bias power supply is 100-300V, the frequency is 30-50kHz, and the pulse width is 3-8μs.
[0066] In some specific embodiments of the present invention, in the sputtering coating step, the bias voltage of the bias power supply is 100-200V, the frequency is 35-45kHz, and the pulse width is 3-7μs.
[0067] In some embodiments of the present invention, the sputtering coating period is 2-3 hours.
[0068] In some specific embodiments of the present invention, the sputtering coating period is 2-2.5 hours.
[0069] In the present invention, a dense layer with high density can be formed on the side close to the substrate through a sputtering coating. The dense layer can effectively prevent oxidation products and corrosive liquid from corroding the substrate and causing cracks, thereby protecting the substrate and improving the corrosion resistance of the coating.
[0070] In some embodiments of the present invention, in the two-stage sputtering coating, the average power density of the high-energy pulsed magnetron sputtering power supply is 0.4-0.8 kw / cm 2 , peak power density is 8-12kw / cm 2 , frequency is 100-600Hz, pulse width is 100-200μs.
[0071] In some specific embodiments of the present invention, in the two-stage sputtering coating, the average power density of the high-energy pulsed magnetron sputtering power supply is 0.4-0.6 kw / cm 2 , peak power density is 9-11kw / cm 2 , frequency is 400-600Hz, pulse width is 100-200μs.
[0072] In some embodiments of the present invention, in the two-stage sputtering coating, the average power density of the DC power supply is 0.5-1.5 kw / cm 2 .
[0073] In some specific embodiments of the present invention, in the two-stage sputtering coating, the average power density of the DC power supply is 0.8-1.2 kw / cm 2 .
[0074] In some embodiments of the present invention, in the two-stage sputtering coating, the bias voltage of the bias power supply is 30-80V, the frequency is 30-50kHz, and the pulse width is 3-8μs.
[0075] In some specific embodiments of the present invention, in the two-stage sputtering coating, the bias voltage of the bias power supply is 40-60V, the frequency is 35-45kHz, and the pulse width is 3-6μs.
[0076] In some embodiments of the present invention, the time for the second-stage sputtering coating is 1.5-2.5 hours.
[0077] In some specific embodiments of the present invention, the time of the second-stage sputtering coating is 1.5-2 hours.
[0078] In the present invention, a relatively low-density loose layer can be formed on the surface of the coating by two-stage sputtering coating, so that the Cr and Al elements in the alloy can form a dense oxide film α-Al under the condition of contacting oxygen. 2 O 3 and Cr 2 O 3 Provide location and self-healing space to improve the self-healing performance of the coating.
[0079] In some embodiments of the present invention, the step S3 includes adjusting the distance between the aluminum-rich substrate and the FeCrAlY magnetron target to 50-100 mm.
[0080] In some specific embodiments of the present invention, the step S3 includes adjusting the distance between the aluminum-rich substrate and the FeCrAlY magnetron target to 70-100 mm.
[0081] In some embodiments of the present invention, in step S3, the annealing temperature is 500-1000° C. and the time is 2-5 hours.
[0082] In some specific embodiments of the present invention, in step S3, the annealing temperature is 600-800° C. and the time is 2-3 hours.
[0083] In some embodiments of the present invention, in step S3, the annealing is performed under an inert atmosphere.
[0084] In some specific embodiments of the present invention, in the step S3, the annealing is performed under an argon atmosphere.
[0085] In some embodiments of the present invention, the method for preparing the FeCrAlY coating specifically comprises the following steps:
[0086] S1. In a magnetron sputtering device provided with a FeCrAlY magnetron target, an Al arc target and a substrate, the distance between the Al arc target and the substrate is adjusted to 5-15 mm, the arc target baffle is closed, the background vacuum degree in the chamber is adjusted and heated, argon gas is introduced to the working gas pressure, the arc target power supply, anode power supply and bias power supply parameters of the device are adjusted, and the substrate is subjected to plasma glow assisted cleaning to obtain an activated substrate;
[0087] S2, turning off the anode power supply, opening the arc target baffle, adjusting the arc target power supply and bias power supply parameters, and injecting Al ions into the activated substrate by arc ion plating and bias assisted attraction bombardment to obtain an aluminum-rich substrate;
[0088] S3, turning off the arc target power supply, adjusting the distance between the FeCrAlY magnetron target and the aluminum-rich substrate, turning on the high-energy pulse magnetron sputtering power supply and the DC power supply, adjusting the parameters of the high-energy pulse magnetron sputtering power supply, the DC power supply and the bias power supply, performing gradient sputtering coating on the surface of the aluminum-rich substrate, and annealing to obtain the FeCrAlY coating.
[0089] The second aspect of the present invention provides a FeCrAlY coating, which is prepared by the preparation method described in the first aspect of the present invention.
[0090] The third aspect of the present invention provides the use of the FeCrAlY coating prepared by the preparation method described in the first aspect of the present invention in lead-bismuth reactor fuel cladding, high-temperature machine tool core components, turbine blades, turbine blades or high-temperature microwave absorption devices.
[0091] Compared with the prior art, the present invention has the following beneficial effects:
[0092] 1) The preparation method of the FeCrAlY coating provided by the present invention can effectively improve the film-base bonding strength by introducing plasma glow assisted cleaning technology to clean and activate the substrate; by pre-embedding and injecting Al elements into the substrate, the pre-embedded Al elements can diffuse to the surface to form a new oxidation protection layer when the coating is worn, so that the coating has self-repairing performance; by adopting a power supply mode mixed with a DC power supply and a high-energy pulse power supply, a high-density, high-ionization rate plasma is generated by a high-power pulse magnetron sputtering technology to ensure the density and uniformity of the coating while improving the deposition efficiency; by combining the gradient coating method, the plasma state is adjusted by using parameter changes, thereby regulating the structure of the film layer, protecting the substrate to reduce corrosion, and reducing internal stress, thereby improving the film-base bonding strength, so that the film layer is not easy to peel off under cyclic thermal stress, and the coating has good heat resistance, good stability, and good corrosion resistance;
[0093] 2) The preparation method of the FeCrAlY coating provided by the present invention makes the preparation process more refined and the coating quality higher by flexibly adjusting the target substrate distance;
[0094] 3) The preparation method of the FeCrAlY coating provided by the present invention has high deposition efficiency and high economic and industrial application value;
[0095] 4) The FeCrAlY coating prepared by the preparation method provided by the present invention has the characteristics of strong film-base bonding, high temperature resistance, corrosion resistance and excellent oxidation resistance, and can meet the application requirements of lead-bismuth reactor fuel cladding, high-temperature machine tool core components, steam turbine blades, turbine blades or high-temperature microwave absorption devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0096] Figure 1 It is a schematic flow chart of the preparation method of the FeCrAlY coating of the present invention;
[0097] Figure 2 It is a schematic diagram of the process of preparing the FeCrAlY coating in the embodiment;
[0098] Figure 3 is a SEM image of the FeCrAlY coating prepared in Example 1;
[0099] Figure 4 is the EDS image of the FeCrAlY coating prepared in Example 1;
[0100] Figure 5 is a SEM image of the FeCrAlY coating prepared in Comparative Example 1;
[0101] Figure 6 The test results of the film-substrate bonding strength of the FeCrAlY coating prepared in Example 1;
[0102] Figure 7 The film-substrate bonding test results of the FeCrAlY coating prepared in Comparative Example 1. DETAILED DESCRIPTION
[0103] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.
[0104] Figure 1 The process diagram of the preparation method of the FeCrAlY coating of the present invention is as follows: Figure 1It can be seen that the preparation method of the FeCrAlY coating provided by the present invention mainly includes three steps: S1 plasma glow assisted cleaning of the substrate, S2 arc ion plating and bias assisted attraction of Al ions to bombard and inject into the substrate, and S3 high-energy pulse and DC composite magnetron sputtering gradient sputtering coating. By adjusting the power supply and other parameters in steps S1-S3, the film coating process can be precisely controlled to obtain a FeCrAlY coating with strong film-base bonding, high temperature resistance, corrosion resistance, excellent oxidation resistance and self-healing performance.
[0105] Figure 2 is a schematic diagram of the process for preparing the FeCrAlY coating in the embodiment, Figure 2 It can be seen that the preparation of the FeCrAlY coating in the embodiment specifically includes S11 pre-treatment of the substrate by grinding, cleaning and drying, S12 installing a FeCrAlY magnetron target, an Al arc target and a substrate in a magnetron sputtering device, adjusting the distance between the Al arc target and the substrate, adjusting the background vacuum and temperature, S13 closing the arc target baffle, filling argon gas to adjust the working gas pressure, S14 adjusting the plasma glow assisted cleaning parameters, cleaning and activating the substrate, S21 opening the arc target baffle, adjusting the arc target power supply and bias power supply parameters, and attracting Al ions to bombard and inject to activate the substrate through arc ion plating and bias assistance, S31 turning on a high-energy pulsed magnetron sputtering power supply (HiPIMS power supply), adjusting the HiPIMS power supply, DC power supply and bias power supply parameters, and performing a first-stage sputtering coating, S32 changing the HiPIMS power supply, DC power supply and bias power supply parameters, performing a second-stage sputtering coating, and S33 annealing.
[0106] The following will be combined Figure 2 The preparation of the FeCrAlY coating in the embodiment is described as follows:
[0107] Example 1
[0108] In this embodiment, FeCrAlY alloy (components are Fe 66.01wt%, Cr 24.8wt%, Al 8.7wt%, Y0.49wt%) is used as a magnetron target, pure Al is used as an arc target, and a FeCrAlY coating is plated on the surface of an austenitic stainless steel substrate. The steps are as follows:
[0109] S11, polish the austenitic stainless steel substrate to a mirror surface, use alcohol and acetone to ultrasonically clean for 10 minutes respectively, and dry for later use;
[0110] S12, place the alloy target and pure Al arc target at the cathode target position and arc target position of the magnetron sputtering equipment respectively, place the substrate in S11 at a position 10 mm opposite to the arc target, and then turn on the vacuum pump. Wait until the vacuum degree in the magnetron sputtering chamber reaches 5×10 -4 Pa, heated to 400°C;
[0111] S13, close the arc target baffle, make the substrate rotate in front of the target, fill with argon gas, and make the pressure in the vacuum chamber reach 1.5Pa;
[0112] S14, turning on the arc target power supply (DC 78A), the anode power supply (DC 50A) and the bias power supply (bias 500V, frequency 100kHz, pulse width 8μs), cleaning for 0.5h to obtain a clean activated substrate;
[0113] S21, turn off the anode power supply, open the arc target baffle, adjust the arc target power supply parameters to DC 100A, adjust the voltage power supply parameters to bias 800V, frequency 100kHz, pulse width 8μs, and use arc ion plating and strong bias voltage to assist in attracting Al ion bombardment injection for 2h, so that Al ions are pre-buried within 2μm below the surface of the substrate to obtain an aluminum-rich substrate;
[0114] S31, turn off the arc power supply, adjust the distance between the FeCrAlY magnetron target and the aluminum-rich substrate to 90 mm, turn on the HiPIMS power supply and DC power supply, and set the HiPIMS power supply parameters to an average power density of 1.0 kW / cm 2 , peak power density 20kw / cm 2 , frequency 200Hz, pulse width 150μs, set DC power supply average power density 1.0kw / cm 2 , adjust the bias power supply parameters to 100V bias, 40kHz frequency, 5μs pulse width, 2.5h sputtering, and 15μm deposited film thickness;
[0115] S32, adjust the HiPIMS power supply parameters to an average power density of 0.6kw / cm 2 , peak power density 10kw / cm 2 , frequency 600Hz, pulse width 100μs, maintain the average power density of DC power supply 1.0kw / cm 2 , adjust the bias power supply parameters to 50V bias, 40kHz frequency, 5μs pulse width, sputtering for 2h, and deposited film thickness of 10μm;
[0116] S33. After the sputtering coating is completed, in-situ annealing is performed in an argon atmosphere for 3 hours at an annealing temperature of 600°C to obtain a FeCrAlY coating.
[0117] Example 2
[0118] In this embodiment, FeCrAlY alloy (components are Fe 67.3wt%, Cr 21.5wt%, Al 10.9wt%, Y0.3wt%) is used as a magnetron target, pure Al is used as an arc target, and a FeCrAlY coating is plated on the surface of an austenitic stainless steel substrate. The steps are as follows:
[0119] S11, polish the austenitic stainless steel substrate to a mirror surface, use alcohol and acetone to ultrasonically clean for 10 minutes respectively, and dry for later use;
[0120] S12, place the alloy target and pure Al arc target at the cathode target position and arc target position of the magnetron sputtering equipment respectively, place the substrate in S11 at a position 12 mm opposite to the arc target, and then turn on the vacuum pump. Wait until the vacuum degree in the magnetron sputtering chamber reaches 1×10 -3 Pa, heated to 300°C;
[0121] S13, close the arc target baffle, make the substrate rotate in front of the target, fill with argon gas, and make the pressure in the vacuum chamber reach 1.0Pa;
[0122] S14, turning on the arc target power supply (DC 70A), the anode power supply (DC 45A) and the bias power supply (bias 400V, frequency 90kHz, pulse width 5μs), cleaning for 0.8h to obtain a clean activated substrate;
[0123] S21, turn off the anode power supply, open the arc target baffle, adjust the arc target power supply parameters to 90A DC, adjust the voltage power supply parameters to 700V bias, 90kHz frequency, and 5μs pulse width, and use arc ion plating and strong bias voltage to attract Al ions for bombardment injection for 1h, so that Al ions are pre-buried within 2μm below the surface of the substrate to obtain an aluminum-rich substrate;
[0124] S31, turn off the arc power supply, adjust the distance between the FeCrAlY magnetron target and the aluminum-rich substrate to 75 mm, turn on the HiPIMS power supply and DC power supply, and set the HiPIMS power supply parameters to an average power density of 0.8 kw / cm 2 , peak power density 18kw / cm 2 , frequency 100Hz, pulse width 100μs, set the DC power supply average power density to 0.8kw / cm 2 , the bias power supply parameters were adjusted to bias 150V, frequency 35kHz, pulse width 3μs, sputtering coating 1.5h, and deposited film thickness 13μm;
[0125] S32, adjust the HiPIMS power supply parameters to an average power density of 0.4kw / cm 2 , peak power density 9kw / cm 2 , frequency 400Hz, pulse width 150μs, maintain the average power density of DC power supply 0.8kw / cm 2 , adjust the bias power supply parameters to bias 40V, frequency 35kHz, pulse width 3μs, sputtering coating 1.5h, deposited film thickness 8μm;
[0126] S33. After the sputtering coating is completed, in-situ annealing is performed in an argon atmosphere for 2 hours at an annealing temperature of 800°C to obtain a FeCrAlY coating.
[0127] Example 3
[0128] In this embodiment, FeCrAlY alloy (components are Fe 60.3wt%, Cr 27.1wt%, Al 12.58wt%, Y0.02wt%) is used as a magnetron target, pure Al is used as an arc target, and a FeCrAlY coating is plated on the surface of an austenitic stainless steel substrate. The steps are as follows:
[0129] S11, polish the austenitic stainless steel substrate to a mirror surface, use alcohol and acetone to ultrasonically clean for 10 minutes respectively, and dry for later use;
[0130] S12, place the alloy target and pure Al arc target at the cathode target position and arc target position of the magnetron sputtering equipment respectively, place the substrate in S11 at a position 8 mm opposite to the arc target, and then start the vacuum pump. Wait until the vacuum degree in the magnetron sputtering chamber reaches 5×10 -3 Pa, heated to 500°C;
[0131] S13, close the arc target baffle, make the substrate rotate in front of the target, fill with argon gas, and make the pressure in the vacuum chamber reach 2.0Pa;
[0132] S14, turning on the arc target power supply (DC 80A), the anode power supply (DC 55A) and the bias power supply (bias 450V, frequency 110kHz, pulse width 10μs), cleaning for 1h to obtain a clean activated substrate;
[0133] S21, turn off the anode power supply, open the arc target baffle, adjust the arc target power supply parameters to DC 110A, adjust the voltage power supply parameters to bias 900V, frequency 110kHz, pulse width 10μs, and use arc ion plating and strong bias voltage to assist in attracting Al ion bombardment injection for 1.5h, so that Al ions are pre-buried within 2μm below the surface of the substrate to obtain an aluminum-rich substrate;
[0134] S31, turn off the arc power supply, adjust the distance between the FeCrAlY magnetron target and the aluminum-rich substrate to 100 mm, turn on the HiPIMS power supply and DC power supply, and set the HiPIMS power supply parameters to an average power density of 1.2 kw / cm 2 , peak power density 22kw / cm 2 , frequency 300Hz, pulse width 130μs, set DC power supply average power density 1.2kw / cm 2 , the bias power supply parameters were adjusted to bias 200V, frequency 45kHz, pulse width 7μs, sputtering coating for 2h, and deposited film thickness 14μm;
[0135] S32, adjust the HiPIMS power supply parameters to an average power density of 0.5kw / cm 2 , peak power density 11kw / cm2 , frequency 500Hz, pulse width 200μs, maintain the average power density of DC power supply 1.2kw / cm 2 , the bias power supply parameters were adjusted to bias 60V, frequency 45kHz, pulse width 4μs, sputtering coating 1.8h, and deposited film thickness 12μm;
[0136] S33. After the sputtering coating is completed, in-situ annealing is performed in an argon atmosphere for 2.5 hours at an annealing temperature of 700°C to obtain a FeCrAlY coating.
[0137] Comparative Example 1
[0138] In this comparative example, the same FeCrAlY alloy as in Example 1 was used as a magnetron target, pure Al was used as an arc target, and a FeCrAlY coating was plated on the surface of an austenitic stainless steel substrate in the following steps:
[0139] S11, polish the austenitic stainless steel substrate to a mirror surface, use alcohol and acetone to ultrasonically clean for 10 minutes respectively, and dry for later use;
[0140] S12, place the alloy target and pure Al arc target at the cathode target position and arc target position of the magnetron sputtering equipment respectively, place the substrate in S11 at a position 10 mm opposite to the magnetron target, make the substrate rotate in front of the target, then turn on the vacuum pump, and wait until the vacuum degree in the magnetron sputtering chamber reaches 5×10 -4 Pa, heated to 400°C;
[0141] S13, filling with argon gas to make the pressure in the vacuum chamber reach 1.5Pa;
[0142] S31, turn on the HiPIMS power supply and adjust the parameters to an average power density of 1.0 kW / cm 2 , peak power density 20kw / cm 2 , frequency 200Hz, pulse width 150μs; adjust the average power density of DC power supply to 1.0kw / cm 2 ; Adjust the bias voltage to 100V, the frequency to 40kHz, the pulse width to 5μs, and the deposited film thickness to 15μm; sputtering for 2.5h;
[0143] S32, adjust the HiPIMS power supply parameters to an average power density of 0.6kw / cm 2 , peak power density 10kw / cm 2 , frequency 600Hz, pulse width 100μs, maintain the average power density of DC power supply 1.0kw / cm 2 , adjust the bias power supply parameters to 50V bias, 40kHz frequency, 5μs pulse width, sputtering for 2h, and deposited film thickness of 10μm;
[0144] S33. After the sputtering coating is completed, in-situ annealing is performed in an argon atmosphere for 2 hours at an annealing temperature of 600°C to obtain a FeCrAlY coating.
[0145] Performance Testing
[0146] 1. The FeCrAlY coatings prepared in Example 1 and Comparative Example 1 were characterized using a scanning electron microscope (SEM) and an energy dispersive X-ray spectrometer (EDS):
[0147] Figure 3 is the SEM image of the FeCrAlY coating prepared in Example 1. Figure 3 It can be seen that the FeCrAlY coating prepared in Example 1 is dense and has a certain layered structure.
[0148] Figure 4 is the EDS image of the FeCrAlY coating prepared in Example 1. Figure 4 It can be seen that a large amount of Al element is enriched at the bottom of the FeCrAlY coating prepared in Example 1, which proves that in Example 1, Al ions are successfully injected into the subsurface of the austenitic stainless steel substrate by bombardment through high-energy arc ion plating and strong bias voltage attraction.
[0149] Figure 5 is the SEM image of the FeCrAlY coating prepared in Comparative Example 1. Figure 5 It can be seen that the FeCrAlY coating prepared in Example 1 has insufficient density and presents a coarse columnar crystal morphology at the bottom.
[0150] The characterization results show that plasma glow assisted cleaning technology and Al element pre-embedded injection are beneficial to improving the internal structure of the coating and enhancing the density of the film layer; when the plasma glow assisted cleaning technology is not used to clean the substrate, and arc ion plating and bias voltage are not used to assist in bombarding and injecting Al elements into the substrate, the density of the FeCrAlY coating will be reduced during the epitaxial growth process, and the coating quality will be reduced.
[0151] 2. The film-substrate bonding strength of the FeCrAlY coatings prepared in Example 1 and Comparative Example 1 was tested:
[0152] Test method reference standard: GBT30707-2014 "Fine ceramic coating adhesion test method scratch method";
[0153] The specific test method is: use a diamond to continuously increase the load (0-100N) and scratch the coating surface until the preset maximum load is loaded. The maximum film-base bonding strength of the coating is obtained by analyzing the peeling position through optical microscopy photos and comparing the friction coefficient and the acoustic signal mutation position.
[0154] Figure 6The test results of the film-substrate bonding strength of the FeCrAlY coating prepared in Example 1, wherein: Figure 6 (a) is a light microscopic photograph of the scratches on the FeCrAlY coating prepared in Example 1. Figure 6 (b) is the test data of membrane-based bonding strength, Figure 6 (b) The values of the load from small to large correspond to Figure 6 The scratch positions from left to right in (a) are Figure 6 It can be seen that Figure 6 (b) When the medium load reaches 80N, Figure 6 The coating at the corresponding position in (a) peels off, indicating that the film-base bonding strength of the FeCrAlY coating prepared in Example 1 can reach 80N, the film-base bonding strength is large, and the wear resistance is good.
[0155] Figure 7 The test results of the film-substrate bonding strength of the FeCrAlY coating prepared in Comparative Example 1 are as follows: Figure 7 It can be seen that when the load reaches about 2N, the coating in Comparative Example 1 begins to peel off, indicating that the plasma glow assisted cleaning technology was not used to clean the substrate, and Al ions were not bombarded and injected into the substrate, so that the lattice and stress matching between the substrate and the coating was not adapted and adjusted, resulting in large coating stress, poor film-base bonding, and easy cracking and falling off.
[0156] The FeCrAlY coating preparation method provided by the present invention has a layered structure, and the loose layer with relatively low surface density is composed of α-Al2O3 formed by Al and Cr elements in the FeCrAlY alloy. 2 O 3 and Cr 2 O 3 The oxide protective film provides a place and self-healing space. The Al element pre-embedded and injected into the substrate can be used as an element supplement to reform the oxide film when the coating is mechanically damaged or stress cracked, thereby realizing self-repair of the coating. The dense layer with higher density close to the substrate can resist the erosion of the substrate by surface oxides and corrosive liquids, effectively protecting the substrate. The coating stress is adjusted by gradient coating, which reduces the possibility of cracking of the coating under cyclic thermal stress. The FeCrAlY coating prepared by the preparation method provided by the present invention has a membrane-base bonding force of up to 80N, good wear resistance, and is not easy to fall off. The FeCrAlY coating has excellent high temperature resistance, corrosion resistance, and wear resistance, and a strong membrane-base bonding force, which can meet the application requirements of lead-bismuth reactor fuel cladding, high-temperature machine tool core components, steam turbine blades, turbine blades, or high-temperature microwave absorption devices.
Claims
1. A method for preparing a FeCrAlY coating, characterized in that: The following steps are involved: S1. In a magnetron sputtering device provided with a FeCrAlY magnetron target, an Al arc target and a substrate, the substrate is subjected to plasma glow assisted cleaning to obtain an activated substrate; S2, using arc ion plating and bias voltage to attract Al ions to bombard and inject into the activated substrate to obtain an aluminum-rich substrate; S3. Using high-energy pulse and DC composite magnetron sputtering method, gradient sputtering coating is performed on the surface of the aluminum-rich substrate, and annealing is performed to obtain the FeCrAlY coating.
2. The preparation method according to claim 1, characterized in that: In the step S1, the FeCrAlY magnetron target includes the following components in mass percentage: Fe 60-70wt%, Cr 20-30wt%, Al 4-20wt%, and Y 0-0.5wt%.
3. The preparation method according to claim 1, characterized in that: The step S1 includes adjusting the distance between the Al arc target and the substrate, adjusting the background vacuum, temperature, working pressure, and arc target power supply, anode power supply and bias power supply parameters of the device, and performing plasma glow-assisted cleaning of the substrate.
4. The preparation method according to claim 3, characterized in that: The distance between the Al arc target and the substrate is 5-15 mm; And / or, the background vacuum degree is 1×10 -5 Pa-1×10 -3 Pa; And / or, the temperature is 200-600°C; And / or, the working gas pressure is 1-4 Pa; And / or, the arc target power supply is DC 60-80A; And / or, the anode power supply is a DC 40-60A; And / or, the bias voltage of the bias power supply is 300-600V, the frequency is 80-120kHz, and the pulse width is 5-12μs.
5. The preparation method according to claim 1, characterized in that: The step S2 includes adjusting the arc target power supply of the device to a DC power supply of 80-120A; And / or, the bias power supply of the device is adjusted to a bias voltage of 700-1000V, a frequency of 80-120kHz, and a pulse width of 5-12μs.
6. The preparation method according to claim 1, characterized in that: In step S3, the gradient sputtering coating at least includes adjusting the parameters of the high-energy pulsed magnetron sputtering power supply, the DC power supply and the bias power supply respectively to perform one-stage sputtering coating and two-stage sputtering coating; the first-stage sputtering coating has a deposited film thickness of 13-18 μm; the second-stage sputtering coating has a deposited film thickness of 5-12 μm.
7. The preparation method according to claim 6, characterized in that: In the above-mentioned sputtering coating, the average power density of the high-energy pulse magnetron sputtering power supply is 0.8-1.5 kw / cm 2 , peak power density is 15-25kw / cm 2 , frequency is 100-600Hz, pulse width is 100-200μs; And / or, the average power density of the DC power supply is 0.5-1.5kw / cm 2 ; And / or, the bias voltage of the bias power supply is 100-300V, the frequency is 30-50kHz, and the pulse width is 3-8μs.
8. The preparation method according to claim 6, characterized in that: In the two-stage sputtering coating, the average power density of the high-energy pulse magnetron sputtering power supply is 0.4-0.8kw / cm 2 , peak power density is 8-12kw / cm 2 , frequency is 100-600Hz, pulse width is 100-200μs; And / or, the average power density of the DC power supply is 0.5-1.5 kw / cm 2 ; And / or, the bias voltage of the bias power supply is 30-80V, the frequency is 30-50kHz, and the pulse width is 3-8μs.
9. A FeCrAlY coating, characterized in that: The method comprises adopting the preparation method described in any one of claims 1 to 8.
10. Application of the FeCrAlY coating prepared by the preparation method according to any one of claims 1 to 8 in lead-bismuth reactor fuel cladding, high-temperature machine tool core components, steam turbine blades, turbine blades or high-temperature microwave absorption devices.
Citation Information
Patent Citations
FeCrAlY coating resistant to high-temperature liquid lead or lead bismuth corrosion and preparation method thereof
CN111020500A
Alloy material with multielement gradient composite coating deposited on surface and preparation method of alloy material
CN111996495A
Preparation method of FeCrAlY wear and corrosion resistant coating based on HiPIMS and ion implantation technology
CN118957527A
Cited By
Laser discharge cavity inner surface coating and preparation method thereof
CN120443127A